ANTIBIOTICS SENSITIVITY TEST DIFFUSION AND DILUTION METHODS - Nadia Elzuhria A; Nur Silmi kaffah; Nafis Rizqi N; Ummi Hanidah; Aisyah Mallika S; Firda Ayu Nabilla; Fajwatunnisa Azkadhafina; Taufiq Ahmad Hidayat; Nadya Fierdini Putri; Putri Alifia Zahra; Tristan Setiawan; Fomaembarasi Buulolo (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
An antibiotic sensitivity test is a method to test the response of bacteria to antibiotics. This study aims to determine the effectiveness of an antibiotic against microbial activity. The sensitivity test was conducted with two methods, namely, the diffusion method and the dilution method. The diffusion method was performed using paper discs (Kirby-Bauer) against Escherichia coli and Shigella sonnei bacteria with amoxicillin, neomycin, and sulfonamide antibiotics. The data required is the diameter of the inhibition zone. Results showed that Escherichia coli was sensitive to amoxicillin but resistant to sulfonamide and neomycin. Meanwhile, Shigella sonnei was resistant to amoxicillin, neomycin, and sulfanilamide. Furthermore, the dilution method was performed to test the potency of amoxicillin against Escherichia coli bacteria using the liquid dilution method. The data required were test tubes with liquid media that showed no turbidity. The results showed that the minimal inhibitory concentration of amoxicillin against Escherichia coli was 0.25%. Based on the results of the antibiotic sensitivity test using the diffusion and the dilution methods, it can be concluded that amoxicillin has high effectiveness against Escherichia coli bacteria with a minimum inhibitory concentration of 0.25%, while Shigella sonnei is resistant to the antibiotics tested.